Pour une agriculture intelligente face au changement climatique au Sénégal: Recueil de bonnes pratiques d'adaptation et d'atténuation - Diouf, B.; Lo, HM; Dieye, B; Sane, O; Sarr, OF (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Climate change is at the present time a new threat which leads to increased frequency and intensity of floods, droughts and cyclones with rising sea levels; thus placing additional demands on a situation already critical in rural areas. In Senegal, as in many countries of the Sahel, those natural phenomena result in a significant drop in harvests, water shortages and worsening health crisis which leads to consequences such as growing food insecurity of the population; thus threatening the progress achieved in regards with the fight against poverty during the last century. Indeed, many farmers live in rural areas which are characterized as low rainfall, saline soils, fragile or degraded soils and limited market access areas. The poverty in which they live, especially those of women, is often worsened by social exclusion. Such farmers are vulnerable because they depend directly on rainfall and seasons. They have little savings while supports from the government or their local authorities remain inadequate. It is essential to strengthen the adaptive capacity of vulnerable countries and communities to cope with the impacts of climate change on agriculture and food security. This document is the result of a multi-criteria analysis of experiences of tackling climate variability, drought and desertification, and land degradation on one hand, and Adaptation to Climate Change in Senegal on the other.